Mechanical properties and reinforcement mechanism study of sulfate saline soil solidified by polyurethane and water glass - Tiantian Zhang; Dingfeng Cao; Chengchao Guo; Fuming Wang (Case Studies in Construction Materials)
Sulfate saline soil is considered as an inferior subgrade construction material that is highly susceptible to damage from salt heaving and dissolution. Polyurethane/water glass (PU/WG) is an efficient grouting material widely used in underground engineering; however, its application in saline soil reinforcement has not yet been reported. In this study, PU/WG was used to solidify sulfate–saline soils. The influence of the dry density, curing agent ratio, and salt content on the strength was evaluated. The mechanical properties of the solidified soil were determined by conducting uniaxial compression strength tests, and crack development was detected using acoustic emission technology. The reinforcing mechanism was revealed by scanning electron microscopy tests and mercury intrusion porosimetry. The results indicated that the peak stress, peak strain, and ultimate strain increased with increasing dry density and PU/WG content, whereas they decreased with increasing salt content. The relationship between the peak stress, density, and PU/WG can be described using linear functions. The relationship between the peak stress and salt content can be described by a second-order polynomial function. The larger the dry density and the higher the PU/WG content, the steeper the stress-strain curves and the lower the ductility. Further, the higher the salt content, the higher the ductility. Soil with a higher dry density, more PU/WG, and less salt content exhibited higher brittleness. Thus, PU/WG can fill in the original disorganized and large pores, thereby increasing the complexity of the internal pore structure via organic-inorganic gel reactions.